The Effectiveness Of Designed Visual Exercise On Attention On Concentration On Complete Strike Skills of Volleyball-Sitting - Mohameed, Sonds; Mohameed, Ghzwan (Journal of Physical Education, 2014)
The study aimed to show the effectiveness of players concentrate on his performance in sport activity. The problem of the research is in the weakness of the skilful performance on the complete strike skill. The two researchers have passed the experienced course by designing one group with the dimension (pre and post which has applied on a sample 12 players and two of them have been excluded in order to make the number of the participated players of Anbar Baralombia committee for volleyball sitting 10 players. The two researchers have explained the details of teaching course after that the post tests have been applied according of the ways of pre-test circumstances by using (T) rule. After that the analysis and discussion of the results have been made in details. The two researchers have concluded that the designed exercises that have been used in the research led to the developing of the players performances in a positive way on the selected skill of this study